2016
DOI: 10.3389/fphys.2016.00512
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotyping Reveals the Diversity of Human Dental Pulp Mesenchymal Stromal Cells In vivo and Their Evolution upon In vitro Amplification

Abstract: Mesenchymal stromal/stem cells (MSCs) from human dental pulp (DP) can be expanded in vitro for cell-based and regenerative dentistry therapeutic purposes. However, their heterogeneity may be a hurdle to the achievement of reproducible and predictable therapeutic outcomes. To get a better knowledge about this heterogeneity, we designed a flow cytometric strategy to analyze the phenotype of DP cells in vivo and upon in vitro expansion with stem cell markers. We focused on the CD31− cell population to exclude end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 59 publications
(104 reference statements)
3
21
2
Order By: Relevance
“…In the present study, Cyagen Human Mesenchymal Stem Cell Growth Medium kits were used to culture the primary dental pulp cells and subsequently, stem cell-related marker expression was detected by ow cytometry. MSCA-1 was expressed by 5.6% of DPSCs, which was consistent with a previous report (21). General high glucose DMEM with fetal bovine serum was used to culture DPSCs, which induced MSCA-1 expression in 1.1% of DPSCs, as determined by ow cytometry.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, Cyagen Human Mesenchymal Stem Cell Growth Medium kits were used to culture the primary dental pulp cells and subsequently, stem cell-related marker expression was detected by ow cytometry. MSCA-1 was expressed by 5.6% of DPSCs, which was consistent with a previous report (21). General high glucose DMEM with fetal bovine serum was used to culture DPSCs, which induced MSCA-1 expression in 1.1% of DPSCs, as determined by ow cytometry.…”
Section: Discussionsupporting
confidence: 91%
“…Ducret et al found an important diminution of CD271 + and STRO-1 + cells (<1%) in the culture expanded MSC populations compared with fresh human dental pulp (37). In addition, the percentage of CD56 + cells strongly increased from P1 (25%) to P4 (80%) in amplified MSC subpopulations from human dental pulp (38). Likewise, in in vitro cultures of normal BM samples changes were noted in the proportion of STRO-1 + and CD73 + MSCs compared with the initial seeded sample.…”
Section: Mesenchymal Stromal Cellsmentioning
confidence: 97%
“…However, MSC amplification in cultures produces changes in their phenotypic and genomic imprinting profiles and distorts their real distribution in comparison with in vivo models (36,37). In addition, the percentage of CD56 + cells strongly increased from P1 (25%) to P4 (80%) in amplified MSC subpopulations from human dental pulp (38). In addition, the percentage of CD56 + cells strongly increased from P1 (25%) to P4 (80%) in amplified MSC subpopulations from human dental pulp (38).…”
Section: Mesenchymal Stromal Cellsmentioning
confidence: 99%
“…CD56 is a cell adhesion molecule which belongs to the superfamily of immunoglobulin receptors. It is abundantly expressed in the central nervous systems and hence it mediates several neuronal functions by controlling intercellular adhesion, neurite outgrowth, and cell migration, proliferation, survival and differentiation; all of which are characteristics of cells migrating from the cephalic neural crest (Ducret et al, 2016 ).…”
Section: Dental Mesenchymal Stem Cells Beyond Regenerative Dentistrymentioning
confidence: 99%
“…They allow for the expression of stem/progenitor cell markers and preserve amplification kinetics without inducing karyotype abnormality while maintaining the differentiation potential of DPSCs into osteoblast/odontoblast cells. Although there are many successful advanced therapies with medicinal products and good regulations from the FDA “21 CFR Part 1271” and the European Medicines Agency (European Directive 1394/2007), further studies are required to determine more specific properties that could be used for the regeneration of human tissues, with standardized cell-based medicinal products (Ducret et al, 2015b , 2016 ).…”
Section: Translational Regenerative Dentistry For the Futurementioning
confidence: 99%